The effect of electric consumption on economic growth in Malaysia / Mohd Zulhaimi Ahmad - Ahmad, Mohd Zulhaimi (2018)
This paper studies about the effect of electric consumption on economic growth in Malaysia by using time series data for the period 1963 until 2017 with 55 observations. There are four types of analyses. The first test was conducted using the OLS to find out the significant of the variables and the relationships between independent variables. Next, unit root test by using ADF and PP test was conducted to find out the stationary of the variables with the level, 1st difference or 2nd difference. After that, Johansen Co-Integration test was conducted to find out whether there is a long-run relationship between the variables. After that, Granger Causality test was conducted to find out whether there is a short-run relationship based from the Johansen Co-Integration test between the specific variable. Lastly, diagnostic tests is conducted to find the relationship between the variables by using the autocorrelation and multicollinearity estimation.